2016
DOI: 10.1007/s10750-016-2996-z
|View full text |Cite
|
Sign up to set email alerts
|

Defining centric diatoms of most relevant phytoplankton functional groups in deep karst lakes

Abstract: Phytoplankton in karst lakes is characterized by co-occurrence of chrysophytes (Chrysophyceae), dinoflagellates (Dinophyceae), and diatoms (Bacillariophyta) as the most diverse and abundant group. Using Reynolds functional approach in ecological phytoplankton investigations makes karstic lakes comparable and facilitates interpretation of their responses to changing environmental conditions. Accurate taxonomic identification to species level, based on precise resolution of specific characteristics by electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 106 publications
(123 reference statements)
1
16
0
Order By: Relevance
“…However, this is most likely a consequence of the generally poor environmental conditions related to the accumulation of muddy sediment in the Cetina River (see Vilenica et al, 2016b). On the contrary, though in markedly lower numbers, a large part of the recorded species in the pristine catchment of the Plitvice Lakes inhabited silt mixed with leaf litter, which could have provided more substantial food resources in the otherwise oligotrophic water quality (Špoljar et al, 2007;Gligora Udovič et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is most likely a consequence of the generally poor environmental conditions related to the accumulation of muddy sediment in the Cetina River (see Vilenica et al, 2016b). On the contrary, though in markedly lower numbers, a large part of the recorded species in the pristine catchment of the Plitvice Lakes inhabited silt mixed with leaf litter, which could have provided more substantial food resources in the otherwise oligotrophic water quality (Špoljar et al, 2007;Gligora Udovič et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, physical conditions and processes within the Plitvice Lakes have been poorly investigated (Klaić et al, 2018). Few studies have reported on the observed physical properties of the lakes, such as lake surface temperatures, water conductivity, and transparency (Gligora Udovič et al, 2017;Sironić et al, 2017). Some authors have discussed lake stratification based only on occasional observations of temperature profiles (Gavazzi, 1919;Petrik, 1958Petrik, , 1961, whereas others have investigated surface seiches (Gavazzi, 1919;Pasarić and Slaviček, 2016) and have reported two possible internal seiche events seen as vertical movements of the isothermal surfaces (Gavazzi, 1919).…”
Section: Introductionmentioning
confidence: 99%
“…1) during its stratification period in 2018. With an altitude of 535 m a.s.l., Kozjak Lake is the 12th lake in the chain and is both the deepest (maximum and average depths of 46 and 17.3 m, respectively) and the largest lake (lake surface area of 0.82 km 2 , and volume of 0.01271 km 3 ; e.g., Babinka, 2007;Gligora Udovič et al, 2017). The lake stretches from south-southeast to north-northwest and has a complex morphometry.…”
Section: Introductionmentioning
confidence: 99%
“…However, physical conditions and processes within the Plitvice Lakes have been poorly investigated (Klaić et al, 2018). Few studies have reported on the observed physical properties of lakes, such as lakes temperatures, water conductivity and transparency (Gligora Udovič et al, 2017;Sironić et al, 2017). Some authors report on lake stratifications based only on occasional observations of temperature profiles (Gavazzi, 1919;Petrik, 1958Petrik, , 1961, while others investigated surface seiches (Gavazzi, 1919;Pasarić and Slaviček, 2016) and mentioned two possible events of internal seiches seen as vertical movements of the isothermal surfaces (Gavazzi, 1919).…”
Section: Introductionmentioning
confidence: 99%
“…1) during its stratification period in 2018. With an altitude of 535 m above sea level (ASL), Kozjak Lake is the twelfth lake in the chain and is both the deepest (maximum and average depths of 46 and 17.3 m, respectively) and the largest lake (lake surface area of 0.82 km 2 , volume of 0.01271 km 3 ) (e.g., Babinka, 2007;Gligora Udovič et al, 2017). The lake stretches from south-southeast to north-northwest and has a complex morphometry.…”
Section: Introductionmentioning
confidence: 99%